2001
DOI: 10.1086/322265
|View full text |Cite
|
Sign up to set email alerts
|

Very Large Array Observations of the H92α Line from NGC 5253 and Henize 2‐10: Ionized Gas around Super Star Clusters

Abstract: We have detected the H92a radio recombination line from two dwarf starburst galaxies, NGC 5253 and He 2-10, using the Very Large Array. Both the line data as well as the radio continuum data are used to model the properties of the ionized gas in the centers of these galaxies. We consider a multidensity model for radio recombination lines and show why previous models, which were based on the assumption of gas at a single density, are valid in many situations. The models show that the ionized gas has a density o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 69 publications
8
34
0
Order By: Relevance
“…Nevertheless, the logarithmic slope between density and size expected from this degeneracy would be −1.5 which is significantly steeper than that observed (see below). The sizes D and densities n e for NGC 5253 and He 2−10 have been modeled also from radio recombination line observations, and are consistent with those inferred from continuum fitting (Mohan et al 2001).…”
Section: Extragalactic Radio Data Setssupporting
confidence: 71%
“…Nevertheless, the logarithmic slope between density and size expected from this degeneracy would be −1.5 which is significantly steeper than that observed (see below). The sizes D and densities n e for NGC 5253 and He 2−10 have been modeled also from radio recombination line observations, and are consistent with those inferred from continuum fitting (Mohan et al 2001).…”
Section: Extragalactic Radio Data Setssupporting
confidence: 71%
“…The Lyman continuum rate for this single source can explain most if not all of the IRAS luminosity of the galaxy, L p IR at 3.8 Mpc ( Turner, Beck, & Ho 2000). 1.8 # 10 L , mation that the radio source is indeed an H ii region came with the detections of a compact mid-IR source with an IR/radio flux ratio characteristic of H ii regions (Gorjian, Turner, & Beck 2001) and narrow radio and IR recombination lines (Mohan, Ananthamariah, & Goss 2001;Turner et al 2003). This is a giant ultracompact H ii (UCH ii) region, similar in properties to Galactic UCH ii regions, but with a much larger ionized volume due to the excitation of thousands of O stars (Turner et al 1998).…”
Section: Introductionmentioning
confidence: 94%
“…The N Lyc core of the supernebula requires the excitation of 1200 O stars. Radio and Brackett recombination line widths are ∼75 km s Ϫ1 , FWHM (Mohan et al 2001;Turner et al 2003). For a cluster of 1200 O7 stars only and a radius of 0.36 pc, and if we assume that the cluster is within the nebula (see § 5), then at the edge of the nebula is ∼15 km s Ϫ1 ; for a Salpeter cluster of stars v esc from O3 to G (1100-1 ), a more likely mass function, it M , is ∼65 km s Ϫ 1 ; and for a Salpeter cluster extending to K-M stars, it is ∼110 km s Ϫ 1 .…”
mentioning
confidence: 99%
“…It is found that the derived range of the free parameters allow for substantial externally stimulated emission as well, but the values of these parameters are not affected significantly due to limits to the continuum brightness temperature. Further details of the modelling procedure have been described in Mohan et al (2001), and references therein. In Sect.…”
Section: A Multi-density Model For the Ionised Gas In Ngc 253mentioning
confidence: 99%